Risāla-yi asṭurlāb-i Kūshyār Gīlānī - Gīlānī, Kushyār b. Labbān, (Miras Maktoob, ISBN: 9789004365452., 2019)
Kushyār (Pers. Kushyār) b. Labbān Gīlānī was a Persian astronomer and mathematician who flourished around 390/1000. All we know about his personal life is that he originated from the region of Gilan in northern Iran, bordering on the Caspian Sea. Given that he is cited in Abū Rayḥān al-Bīrūnī's (d. after 442/1050) Kitāb fī ifrād al-maqāl fī amr al-aẓlāl , Kushyār must have become an authority by the time al-Bīrūnī came to write this work. From his works in mathematics, Kushyār's Kitāb fī uṣūl ḥisāb al-Hind on Indian arithmatic is the most important, and in astronomy his Zīj-i jāmiʿ . His Arabic work on the astrolabe is published here for the very first time, accompanied by a Japanese translation, both by Taro Mimura of Japan. In addition, this volume also contains a facsimile edition of the anonymous medieval Persian translation of this work, followed by a critical edition, both by Mohammad Bagheri of Iran.